2018
DOI: 10.1007/s10072-018-3558-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between epilepsy and headache

Abstract: The prevalence of headache and the prevalence of migraine, which are considered to be pathogenetically linked to epilepsy, were not different in epilepsy patients as compared to that of the general population. Different outcomes and percentages in other studies suggest that pathogenesis of headache is multifactorial and that different diagnostic criteria might have been taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…A more recent meta-analysis (including studies published between 2004 and 2019) estimated a 49% prevalence of unspecified headache among people with epilepsy 9 . Additional evidence has confirmed the findings of these meta-analyses regarding the co-existence of epilepsy and headache (Table 1) [10][11][12][13][14][15][16][17][18][19] . In these studies, ≤79% of individuals with epilepsy reported experiencing headaches.…”
Section: [H1] Epidemiological Evidencesupporting
confidence: 72%
See 2 more Smart Citations
“…A more recent meta-analysis (including studies published between 2004 and 2019) estimated a 49% prevalence of unspecified headache among people with epilepsy 9 . Additional evidence has confirmed the findings of these meta-analyses regarding the co-existence of epilepsy and headache (Table 1) [10][11][12][13][14][15][16][17][18][19] . In these studies, ≤79% of individuals with epilepsy reported experiencing headaches.…”
Section: [H1] Epidemiological Evidencesupporting
confidence: 72%
“…In these studies, ≤79% of individuals with epilepsy reported experiencing headaches. The most common headache types in individuals with epilepsy were migraine (reported by ≤25% of participants) and TTH (reported by ≤40% of participants) 10,13,14,16,18 .…”
Section: [H1] Epidemiological Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…This finding was similar to findings from the Epilepsy Family Study of Columbia University were the relative risk of migraine and stroke was 2.4 [58]. A large Scottish analysis that found that epilepsy occurred in 2.0% of the migraine group and 0.9% in the nonmigraine group (OR 2.19 [1.89, 2.54]) [36] However, in an analysis of patients with epilepsy who were asked if they have headache, the prevalence of migraine was 15% and was similar to prevalence figures in the general population, but far less than that observed in this analysis [59]. Overlapping mechanisms in epilepsy and migraine, such as mutations in genes for ion channels or neurotransmitter systems may contribute to comorbidities [60].…”
Section: Neurologic Conditionsmentioning
confidence: 41%
“…Learning is one cognitive issue or a consequence and learning problems that lead to an major obstacle to get educational and professional success (66); Psychiatric comorbidities refer to behavior and mood problems, such as bipolar disorder, attention deficit hyperactivity disorder (ADHD), depression, anxiety disorders and autism (66). Neurological comorbidities are migraine headache (69), sleep disorders, such as sleep apnea, insomnia, restless legs syndrome, and the parasomnias (70), pain (neuropathic pain, fibromyalgia, chronic pain) and other (asthma, diabetes, and high blood pressure) (71). The comorbidities are frequent seen in patients with epilepsy, and can deteriorate quality of life further than seizures themselves do (18).…”
Section: Comorbidities Associated With Epilepsymentioning
confidence: 99%